Effect of entanglements in the microstructure of cured NR/SBR blends prepared by solution and mixing in a two-roll mill. (August 2016) - Mansilla, M.A.; Valentín, J.L.; López-Manchado, M.A.; González-Jiménez, A.; Marzocca, A.J.
Graphical abstract: Highlights: Preparation methodology influences the blend morphology and network structure. Better compatibility between rubber phases has been obtained via solution blending. Disentanglement effects on rubber solutions determine the blend morphology. Mechanical blending promotes preferential migration of curatives to NR phase. Abstract: The influence of preparation methodology of vulcanized elastomeric blends of natural rubber (NR) and styrene butadiene rubber (SBR) on the phase morphology and network structure has been studied. Two different compounding methodologies have been applied: (i) mechanical mixing in a two-roll mill and (ii) blending in solution, by dissolving the elastomers in an appropriated solvent. Samples with different NR/SBR ratios were vulcanized by using a conventional cure system based on sulfur and TBBS (n-t-butyl-2-benzothiazole sulfenamide) as accelerator. The phase distribution of rubber matrices in the blends was investigated by transmission electron microscopy (TEM), identifying differences in the compounds according to the preparation method. Weak residual dipolar couplings caused by the existence of cross-links and topological constraints in vulcanized samples were characterized by using proton multiple-quantum (MQ) NMR spectroscopy. The structural results obtained by NMR and equilibrium swelling experiments were compared and complemented with viscosity measurements. It was found that the preparation method has a strong influence on the phase morphology of blends and the molecular network structure of each rubber phase, with an important variation in the entanglements contribution, which is more pronounced when the prepared blends are richer in NR.